(untitled) (CIPEEX, 2025)
INTRODUCTION: As a multifaceted disease, an in-depth understanding of the sociodemographic and clinical profile of patients with Systemic Lupus Erythematosus (SLE) is crucial to optimize diagnosis and care management. OBJECTIVE: To characterize the variables related to the sociodemographic and clinical profile of SLE patients. METHODS: This was a cross-sectional, descriptive, and observational study with a quantitative approach. Data were collected from SLE patients in August 2025 through an online questionnaire (Google Forms). RESULTS: From 34 responses, there was a predominance of females (97.1% – 33/34) and a higher age concentration between 18–30 years (35.3% – 12/34) and 31–40 years (32.4% – 11/34). Although 38.2% (13/34) reported a family income of 1–2 minimum wages, most diagnoses occurred in private clinics (70.5% – 23/34), with smaller proportions in public hospitals (29.4% – 9/34) and particularly in primary care (8.8% – 2/34), indicating limited capacity of primary care for suspicion, investigation, and timely diagnosis. Clinically, more than half of patients (55.9% – 19/30) presented comorbidities, the most prevalent being Hypertension (47.4% – 9/19), fibromyalgia (31.6% – 6/19), depression (15.8% – 3/19), rheumatoid arthritis (10.5% – 2/19), and Antiphospholipid Syndrome (10.5% – 2/19). Half of the patients (50% – 17/34) had been living with SLE for more than six years, and in 47.1% (16/34), the interval between symptom onset and diagnosis exceeded one year. Additionally, access to treatment emerged as a significant barrier: 47.1% (16/34) reported not having regular and free access, and 91.2% (31/34) stated that treatment causes a moderate to high financial burden. Thus, consistent with the literature, the study outlines a profile marked by female predominance in young age, high comorbidity burden, and, above all, barriers in access and resolution within the public health system, particularly in primary care, contributing to diagnostic delay. CONCLUSION: The sociodemographic and clinical profile identified highlights a persistent challenge in the journey of SLE patients: difficulty in accessing timely diagnosis. The predominance of diagnoses in private clinics, the financial burden associated with the treatment, the delay in definitive diagnosis, and the fragility of primary care underscore the need to restructure care pathways to mitigate delays and their consequences, ensuring that the patient’s journey is guided by continuous and resolutive care rather than obstacles.